(untitled) (Experimental biology, 2023)
For the first time, information is provided on the morphological variability and state of the population of the spotted thicklip loach Triplophysa staruchii (Kessler, 1874) in the Shayan River (Syrdarya basin). Morphobiological analysis was carried out according to the standard scheme with some additions. The variability of 44 plastic and 16 counting signs, size-weight indicators and fatness over time was studied. Statistical processing is carried out by the univariant method and using the analysis of the main components. Based on the analysis of external morphological features and the structure of the digestive system, it was found that the studied fish from the Shayan river belong to the species spotted thicklip loach. Samples of different years are represented by different-sized individuals, which indicates sufficient conditions for reproduction and survival. In 2013 and 2020, there was a deterioration in nutritional conditions, which led to a decrease in size, a decrease in the reserves of abdominal fat and fatness coefficients. However, individual values of fatness indicators vary greatly, which may indicate intraspecific competition for food items. Small values of the coefficient of asymmetry (KA) indicate the stability of individual development. The most likely reason for the decline in the number of spotted thicklip loach in 2022 is that it may be dry in summer due to a significant decrease in water level and an increase in water temperature. Annual fluctuations in precipitation are also characteristic of the natural range, so the probability of survival of the spotted thicklip loach in the Shayan River seems to be high.